Son-Rise-Based Floortime Model to Improve Social Skills of Autistic Children: Model Floortime Berbasis Son-Rise untuk Meningkatkan Keterampilan Sosial Anak Autis - Rahma Yunaini; Sunardi Sunardi; Joko Yuwono (ITScience (Information Technology and Science), 2026)
Children with autism often experience difficulties with greeting, eye contact, sharing, turn-taking, emotional expression, and reciprocal communication. At the same time, special education teachers require a structured instructional guidebook to organize these skills into classroom learning and support social participation. This study aimed to develop and preliminarily evaluate a Son-Rise-based Floortime learning model for supporting children’s social development. A Research and Development approach using the 4D stages of define, design, develop, and disseminate was employed. The needs analysis involved five children, three teachers, two parents, and one principal. Three experts assessed feasibility, three teachers evaluated practicality, and a developmental trial was conducted over four meetings with five children after a preliminary trial involving three of them. Data were collected through observation, semi-structured interviews, questionnaires, field notes, and documentation and were analyzed qualitatively and descriptively using percentages, mean scores, raw score increases, indicator-level changes, and meeting-based development. The guidebook integrated engagement, interaction, communication, expansion, and reflection. Expert validation averaged 91.67%, teacher practicality reached 90.83%, and mean social-skills scores increased from 10.8 to 11.8, 13.8, and 14.8 across four meetings. The model was feasible, practical, and showed preliminary promise in supporting children’s social skills. However, the small sample, single-school setting, and absence of a comparison group limit causal interpretation and generalizability.